Indigenous Ways of Creating Environmental Awareness: Case Study from Berekum Traditional Area of Ghana - Awuah-Nyamekye, Samuel (Journal for the study of religion, nature and culture, 2014)
The people of Berekum Traditional Area, Brong Ahafo region, Ghana, use their religio-cultural practices to instil and impart traditional ecologi-cal knowledge to their youth. Qualitative methodology research identi?ed the main means by which indigenous ecological knowledge is transmitted to students: proverbs, myths, folktales, and rituals. There is evidence that indigenous methods of imparting ecological knowledge and thereby dealing with environmental problems are facing some chal-lenges that appear to have interfered with their effectiveness. These challenges may be attributed to a change in the people’s worldview resulting from cultural contact and modernity. The ?ndings indicate that indigenous ecological knowledge is a potential resource that can complement scienti?c means of dealing with the region’s environmental problems.